Protective effect of alirocumab, a PCSK9 inhibitor, on the sciatic nerve of rats with diabetic peripheral neuropathy - Lu, Xiuyan; Chen, Yinghui; Cui, Na; Feng, Yonghao; Shi, Xiaohong; Wang, Ming; Huang, Yongmei (Endocrine Journal, 2024)
Dyslipidemia has been considered a risk factor for diabetic peripheral neuropathy. Proprotein convertase subtilisin-like/Kexin 9 inhibitor (PCSK9) inhibitors are a new type of lipid-lowering drug currently in clinical use. The role of PCSK9 in diabetic peripheral neuropathy is still unclear. In this study, the effect of alirocumab, a PCSK9 inhibitor, on the sciatic nerve in rats with diabetic peripheral neuropathy and its underlying mechanisms were investigated. The diabetic peripheral neuropathy rat model was established by using a high-fat diet combined with streptozotocin injection, and experimental subjects were divided into normal, diabetic peripheral neuropathy, and alirocumab groups. The results showed that Alirocumab improved nerve conduction, morphological changes, and small fiber deficits in rats with DPN, possibly related to its amelioration of oxidative stress and the inflammatory response.